#TITLE_ALTERNATIVE# - RAHMAH (NIM : 22204008), KURNIA
At present, hydrocarbon exploitation is more focused on the development of offshore fields especially that of deepwater since on-shoreÃ‚Â’s petroleum reserves are decreasing dramatically. Oil production from deepwater off-shore needs flow assurance in its pipeline system to be technically reliable and economically feasible. One major problem in producing oil from deepwater off-shore is flow blocking in the pipeline system caused by mechanical failure, hydrate formation, and paraffin wax deposition. Precipitation and/or deposition problem of paraffin wax in underseawater transportation system is very costly such that it significantly increase the operating cost and could cause the company to loss billion of dollars each year. This research focuses on studying flow assurance in deepwater pipeline system or more specifically on the prediction of locations along the pipeline where paraffin wax deposition may occur. The objective of this research is to develop a methodology to ensure that the flow of production fluid within the pipeline is free of blocking caused by wax deposition. The study then developed program that can be used to conduct such prediction that we can detect the location of wax deposition. This could help improving the design of pipeline installation of off-shore operations. Besides, the program developed could also be used to analyze the performance of production pipeline facilities and prevent wax deposition by adjusting parameters that affect the occurrence of wax deposition. Wax solid deposition must be related to cloud point temperature. To prevent the formation of wax, one first should determine the cloud point of the produced fluid. This temperature is very much affected by molecular weight and weight fraction of heavy hydrocarbon component and apparent molecular weight of the mixture. Based on the calculated cloud point, the distribution of pressure and temperature along the flow lines is then determined such that the location of paraffin wax precipitation could be predicted. The program is developed based on the above mentioned principle. The program can be used to compute cloud point with fluid composition as the input. It can also then be used to compute pressure and temperature along the pipeline. The deposition of paraffin wax is predicted based on the value of temperature distribution and critical temperature for specific flow rate, pipe diameter, hydrocarbon composition, and operating condition. The developed program has been verified using commercial software. Although the equation and inputs data have been slightly different, the obtained results match satisfactorily.